Development of Sigamel Mobile Learning for Learning Javanese Noun Vocabulary - Anjarsari, Silfa; Astuti, Eka Yuli (Universitas Pendidikan Mandalika, 2024)
Reading is an important aspect of learning a language. One of the basic aspects of reading is the large vocabulary. Students' vocabulary acquisition can be obtained from the learning process. However, in the vocabulary learning process, problems are still caused by the limitations of the media used. The limited media used causes students' interest in learning to decrease. Responding to these problems, this research aims to develop mobile learning which can be used as an aid for learning the vocabulary of object names from gamelan musical instruments. In developing mobile learning, the research method used is research and development (R&D). The research subjects in this study are teachers, media experts, and material experts. Data collection techniques used interview techniques and questionnaire techniques. Sigamel mobile learning was developed based on analysis of problems, needs, and revisions based on expert validation results. The design validation results obtained a score of 4 from material experts in the good category while the score obtained from media experts was 4.7 in the very good category. The development of Sigamel mobile learning is worthy of being developed in Javanese language learning. The results of this research state explicitly that sigamel mobile learning can be developed into a tool for learning Javanese which focuses on noun vocabulary material. Therefore, teachers are advised to use sigamel mobile learning in learning.